The Effect of Creation Song on Students’ Vocabulary Mastery (Conference on English Language Teaching, 2025)
This study aimed to examine the impact of creation song on vocabulary mastery among fourth-grade elementary school students. Following validation by two experts regarding its content and quality, the developed media implemented at SDN 04 Belik Pemalang, engaging 29 students. The study employed a quasi-experimental design alongside a quantitative research methodology. The findings of the study demonstrated that the creation song significantly enhanced vocabulary mastery among fourth-grade students, as evidenced by the average learning outcomes increasing from 39.86 prior to the treatment to 78.89 following the treatment. Furthermore, the independent sample t-test revealed that the t-count vale surpassed the t-table value, suggesting that the creation song positively influences students’ vocabulary mastery. The N-gain value achieved was 78.09% surpassing the objective value of 76%. This indicates that the implementation of the creation song is highly effective